Estimulación cognitiva como estrategia psicopedagógica para mejorar la atención y memoria en un estudiante con déficit de atención de noveno grado de la Unidad Educativa Particular Juan Montalvo, periodo 2023-2024 - Betancourt Sánchez, Jhon Fernando (2024)
The present curricular integration work aims to propose a guide of cognitive stimulation activities to enhance attention and memory in a ninth-grade student with attention deficit at Unidad Educativa Particular Juan Montalvo. For this purpose, a qualitative, phenomenological, descriptive, and cross-sectional case study was conducted, based on the following research techniques: a semi-structured interview with the student's teachers, administration of the Memory Test (Primary and Secondary Education), the CARAS-R test, and a literature review on the topic of cognitive stimulation. The results showed that teachers have different conceptions and knowledge regarding attention deficit and cognitive stimulation, that the student performs poorly in immediate memory but well in selective attention and mental concentration. Various cognitive stimulation activities were found to benefit students with attention deficit. Based on these findings, a guide of cognitive stimulation activities comprising 10 sessions was developed, each with its objectives, activities, materials, and instructions. The activities are designed to stimulate and improve cognitive functions related to attention and memory, employing resources such as gamification, humor, and art. It is concluded that the guide of cognitive stimulation activities is a useful and practical tool for teachers, enabling them to work with attention deficit students in an adapted, enjoyable, and meaningful manner. Moreover, it is expected that the proposed guide will contribute to enhancing academic performance, emotional well-being, and quality of life for the student, while also strengthening their self-esteem, self-control, and motivation for learning.